Insurgentes - Sanjinés, Jorge; Sanjinés, Jorge; Zarzyka, Danuta; Paucara, Froilán; Achirico, Lucas; Aduviri, Luis; Bustillos, Mónica; Gonzales, Primitivo; Yujra, Reynaldo; Choquehuanca, Roberto; Guimarães, Alice (Actress); Zárate, Alejandro; et al. (Fundación Grupo Ukamau, 2012)
Through recreation of historical events, this is the story of Bolivia's indigenous people's struggle for their sovereignty, lost due to Spanish colonization and oppression. Bolivian heroes, whose stories are absent in official history, are finally told. Their struggle ultimately culminates in the rise of an indigenous person to the Presidency of Bolivia